Eksplorasi Transkultural Perilaku Pemberian Makan Balita: Studi Kualitatif di Masyarakat Pesisir - Ni Luh Agustini Purnama; Veronica Silalahi; Baswara Yua Kristama (Universitas Malahayati, 2026)
ABSTRACT Feeding behavior in children under five years is an important factor in nutritional needs that influence nutritional status and subsequent eating behavior. Parents' feeding behavior is also influenced by culture. The purpose of this study was to explore feeding behavior in children under five years in the context of coastal communities using a qualitative approach based on transcultural nursing theory. This study is qualitative in nature, employing a participatory action research approach. Ten mothers with children under five, two Posyandu cadres, and one midwife from Desa Gisikcemandi, Sidoarjo, participated in this study. Participants were selected using purposive sampling techniques. Data collection was conducted using focus group discussions (FGD) and in-depth interviews. The interview and FGD guides were developed based on the 7 components of the Sunrise Model from the transcultural nursing theory to explore parents' perceptions regarding feeding behaviors. The study identified 4 themes: feeding strategies for children, utilization and management of marine resources, economic and nutritional health challenges, and responses to health interventions. Keywords: Feeding, Under Five Years, Transcultural. ABSTRAK Perilaku pemberian makan pada Balita merupakan salah satu faktor penting untuk memenuhi kebutuhan nutrisi sehingga mempengaruhi status gizi dan perilaku makan anak selanjutnya. Perilaku orang tua dalam pemberian makan pada anak juga dipengaruhi budaya. Tujuan penelitian mengeksplorasi secara mendalam perilaku pemberian makan balita dalam konteks budaya masyarakat pesisir melalui pendekatan kualitatif berbasis teori keperawatan transkultural. Desain penelitian kualitatif dengan pendekatan participatory action research. Partisipan dalam penelitian ini adalah 10 orang ibu yang memiliki Balita, 2 kader posyandu dan 1 Bidan Desa di Desa Gisikcemandi Sidoarjo. Pemilihan partisipan dengan tehnik purposive sampling. Pengumpulan data dengan tehnik focus group discussion (FGD) dan wawancara mendalam. Panduan wawancara dan FGD disusun berdasarkan 7 komponen Sunrise Model dari teori transcultural nursing untuk mengeksplorasi persepsi orang tua terkait perilaku dalam pemberian makan. Hasil penelitian ditemukan 4 tema yaitu strategi pemberian makan anak, pemanfaatan dan pengelolaan sumber daya laut, tantangan ekonomi dan kesehatan gizi dan respon terhadap intervensi kesehatan. Kata Kunci: Pemberian Makan, Balita, Transkultural.